Peran Kebijakan Pemerintah dalam Mencegah Kecurangan Laporan Keuangan: Tinjauan terhadap Permenkop No.2 Tahun 2024 - Kusumaningsih, Ambar (Politeknik Raflesia Press, 2024)
Cooperatives play a crucial role in Indonesia's economy, however, their unique organizational structure presents risks for financial statement fraud, exacerbated by pressures to maximize member benefits and the lack of stringent oversight mechanisms. The aim of this study is to analyze the role of government regulation in preventing financial statement fraud within cooperatives, specifically examining the implications of Government Regulation No. 2 of 2024 on regulatory effectiveness and fraud prevention mechanisms. This study employs a qualitative approach, focusing on document analysis. Data are analyzed using content analysis techniques to identify themes related to fraud prevention mechanisms, supported by triangulation with relevant literature. Utilizing the fraud triangle theory, it analyzes how the regulation's enhanced transparency, accountability, and reporting standards can mitigate fraud opportunities. The regulation mandates periodic financial reporting, strict measurement and disclosure standards, and audits by registered public accountants. Despite its potential effectiveness, challenges in implementation persist, particularly for small cooperatives lacking resources and technological infrastructure. This study emphasizes the need for capacity-building measures, technology improvements, and cultural shifts toward transparency to ensure successful regulation implementation, ultimately protecting cooperative stakeholders and enhancing the integrity of the sector.